Determinan Kualitas Informasi Akuntansi Pada Badan Kepegawaian Daerah Deli Serdang - Ratna Sari Dewi (KITABAH: Jurnal Akuntansi dan Keuangan Syariah, 2019)
The purpose of this study is to analyze the influence of the use of information technology, user expertise and intensity of use on the quality of accounting information. Research Design uses quantitative descriptive research. The total population is 48 people and those chosen as samples in the study amounted to 32 employees. This study uses employees who use IT at the Deli Serdang Regional Personnel Agency as a sample. Testing the hypothesis in this study uses Multiple Linear Regression Analysis with the help of the SPSS program and a significance level of 5% (0.05). The results of testing are partially 1). There is a significant effect of the use of information technology on the quality of accounting information, 2). There is no significant effect of the use of information technology on the quality of accounting information 3). There is no significant effect on the quality of accounting information usage and 4). There is the influence of the use of information technology, user expertise and the intensity of simultaneous use of the quality of accounting information.